NEUTRON ACTIVATION ANALYSIS OF ND-FE-B MAGNET AND DETERMINATION OF THE CONTENT OF ND AFTER OXALATE PRECIPITATION AND PRODUCTION OF ND2O3 - CHERAITIA, K; LOUNIS, .; MEHENNI, M; AZZAZ, M; OSMANE, K (MATTER: International Journal of Science and Technology, 2015)
In practice, the properties of the neodymium magnets are highly dependent on the precise composition of the alloy and its microstructure. The aim of our work is to determine the content of neodymium and the impurities of a magnet Nd-Fe-B. The first step is to analyze the impurities from a super Nd-Fe-B magnet. We used the following techniques: The neutron radiography, the neutron activation analysis (NAA) and the scanning electron microscope coupled with EDX. The samples of Nd-Fe-B and standards are weighed and packed in polyethylene envelopes. They are simultaneously irradiated in thermal reactors column (NUR Draria-Algiers) under a neutron flux of 3.4x1012n/cm²/s. The radioactivity of the samples is measured using a spectrometry chain (hyper pure germanium detector Hp/Ge). Gamma () spectrum is presented in the energy range between 100keV and 2000keV. The detected elements are: Ni, Al, Ti, Cu, Mn, In, Ta, Ce, Sm, Eu, Np, Yb, Gd, and Lu. The digital processing of the images obtained by the neutron radiography shows that in the Nd-Fe-B matrix, the distribution of elements is homogeneous. The SEM micrographics show three different phases of contrasts: light, gray and black which correspond to Nd, Fe, and B. In a second step the powder is dissolved in hydrochloric acid solution. We add an oxalic acid solution to precipitate Nd as neodymium oxalate. The identification of the most intense peaks in the XRD spectrum shows the presence of a single compound which hydrated neodymium oxalate chemical formula Nd2(C2O4)3.10H2O. Its purity is measured by neutron activation analysis. The counting of γ spectrum shows that the purity of the precipitate is higher than 99%. Then, the thermal decomposition transforms this powder to neodymium oxide. After the reduction we obtain pure neodymium. The analytical balance shows that this magnet contains 26% of neodymium.